Evaluation of Class III Malocclusions Through Coben Cephalometric Analysis - Mustafa Ülgen; Cengiz Yolalan (Galenos Yayinevi, 1988)
The purpose of this investigation is to study the morphology of the Angle Class III malocclusions. For this purpose the group of Class III malocclusion was compared to the control group of the ideal occlusion. This study is based on the cephalographs of 40 young adults. 20 cases (10 females, 10 males) were showing Class III malocclusion with anterior crossbite and the other 20 cases (10 females, 10 males) ideal occlusion. In this investigation twelve parameters of the Coben cephalometric analysis were measured, recorded and statistically assessed. The retrognathie superior was found as a significant difference in the Class III malocclusion when compared to the ideal occlusion group.